Current advances in the functional studies of fatty acids and fatty acid-derived lipids in C. elegans. Issue 3 (2nd July 2016) - Ying, Lu; Zhu, Huanhu
ABSTRACT: Fatty acids and fatty acid-derived lipids (FAs/FADLs) play essential roles in many living organisms, including contributions to membrane structure and signaling transduction. Aberrant metabolism of FAs/FADLs often causes diseases and health problems. However, the detailed mechanistic studies of specific FAs/FADLs in vivo are limited. C. elegans has been an effective model system for FA/ FADL studies due to its powerful genetics and conserved lipid biosynthetic pathways. The recently developed high-throughput analytic tools also enable sophisticated profiling of lipids molecules in C. elegans, which is critical for understanding their specific functions. Here we review a subset of current advances in FA/FADL functional studies in C. elegans .